Cururu e siriri : das festas de santo à circulação institucional na grande Cuiabá - Pinto, Carlos Benedito (2016)
In the Metropolitan Region of the Cuiabá River Valley (Região Metropolitana do Vale do Rio Cuiabá), in Mato Grosso, the circulation of cururu and siriri, traditional cultural manifestations of the “Baixada Cuiabana”, show the ambiguities of the protagonism of marginalized manifestations of popular culture in contemporary way of life. The traditional manifestations, in a society that expands in population terms, are subjectived in the middle of the project of national insertion in the global economy, evidencing the conflicts between tradition and modernity. This dissertation aims to narrate the circulation of the cururu and the siriri in the path that goes from the catholic holy feasts, its traditional place, to the events that come to demand the symbolic aspects of the traditions in the experience of metropolization of the city of Cuiabá. Based on the empirical data, we try to reflect on the contradictions and the updating of these intagible good from the perspective of the communicational field in its interface with the cultural field. As a central issue, we consider the cultural practices in the urban experience of the so-called Grande Cuiabá (Large Cuiabá) and the appeal to traditions as a search for an idea of singularity in the emerging metropolis that gains the air of a generic city. We promote the collection of data through bibliographic research and field research, accompanying the circulation of these cultural practices in the urban conurbation of Cuiabá and Santo Antônio de Leverger, municipalities in the RMVRC, in the year 2013.